KORELASI ANTARA PENGGUNAAN GADGET DI RUMAH DENGAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI PAUD DELLIA CREATIVE SCHOOL - Try Yuniata Damayati; Agus Zainal; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2020)
Innovation of the latest technology with better capabilities and latest features that have the purpose or function to be more practical and useful or gadget. As it grows, the definition of gadget is growing into a wider anyway. Many people assume that smartphone is a gadget. There is also a thought that the computer or laptop with new technology is gadget. The purpose of this study was to determine the correlation between the used of gadget at home with social emotional development of children aged 3-5 years in PAUD Dellia Creative School. This research used a correlational study with quantitative approach. Samples were taken by using purposive sampling as many as 37 respondents.The instrument used in this study was a questionnaire, by using indirectly questionnaires. The statistical test by using the formula of product moment correlation, with an error rate (?) = 0.05. The research results get the value of tcount is 1.26 and ttableis 1.6905. Value of correlation between the used of gadget with social emotional development of children aged 3-5 years is 0.21, which means the correlation is very low. The conclusion of this research that there is no significant correlation between the used of gadget at home with social emotional development of children aged 3-5 years in PAUD Dellia Creative School. Key words: Correlation, The used of gadget, Social Emotional Development of Children.